Masting mediated by summer drought reduces acorn predation in mediterranean oak forests - Espelta, Josep Maria; Cortés, Pilar; Molowny-Horas, Roberto; Sánchez-Humanes, Belén; Retana, Javier (ECOLOGY, 2008)
Temporally variable production of seed crops by perennial plants (masting) has been hypothesized to be a valuable mechanism in the reduction of seed predation by satiating and starving seed consumers. To achieve these benefits, coexisting species subjected to the same predator would benefit from a similar pattern of seeding fluctuation over time that could lead to a reduction in predation at the within-species level. We tested for the existence of an environmental factor enforcing synchrony in acorn production in two sympatric Mediterranean oaks ( Quercus ilex and Q. humilis) and the consequences on within-species and between species acorn predation, by monitoring 15 mixed forests (450 trees) over seven years. Acorn production in Q. ilex and Q. humilis was highly variable among years, with high population variability (CVp) values. The two species exhibited a very different pattern across years in their initial acorn crop size ( sum of aborted, depredated, and sound acorns). Nevertheless, interannual differences in summer water stress modified the likelihood of abortion during acorn ripening and enforced within-and, particularly, between-species synchrony and population variability in acorn production. The increase in CVp from initial to mature acorn crop ( after summer) accounted for 33% in Q. ilex, 59% in Q. humilis, and 60% in the two species together. Mean yearly acorn pre-dispersal predation by invertebrates was considerably higher in Q. humilis than in Q. ilex. Satiation and starvation of predators was recorded for the two oaks, and this effect was increased by the year-to-year variability in the size of the acorn crop of the two species combined. Moreover, at a longer time scale ( over seven years), we observed a significant reduction in the mean proportion of acorns depredated for each oak and the variability in both species' acorn production combined. Therefore, our results demonstrate that similar patterns of seeding fluctuation over time in coexisting species mediated by an environmental cue ( summer drought) may contribute to the reduction of the impact of seed predation at a within-species level. Future research should be aimed at addressing whether this process could be a factor assisting in the coexistence of Q. ilex and Q. humilis.
The following values have no corresponding Zotero field: pub-location: 1990 M STREET NW, STE 700, WASHINGTON, DC 20036 USA publisher: ECOLOGICAL SOC AMER
Keywords: Curculio spp.; fruit abortion; fruiting synchrony; Mediterranean mixed-oak forests; oaks; predator satiation; Quercus humilis; Quercus ilex; resource matching

Masting mediated by summer drought reduces acorn predation in mediterranean oak forests - Espelta, Josep Maria; Cortés, Pilar; Molowny-Horas, Roberto; Sánchez-Humanes, Belén; Retana, Javier (ECOLOGY, 2008)
Temporally variable production of seed crops by perennial plants (masting) has been hypothesized to be a valuable mechanism in the reduction of seed predation by satiating and starving seed consumers. To achieve these benefits, coexisting species subjected to the same predator would benefit from a similar pattern of seeding fluctuation over time that could lead to a reduction in predation at the within-species level. We tested for the existence of an environmental factor enforcing synchrony in acorn production in two sympatric Mediterranean oaks ( Quercus ilex and Q. humilis) and the consequences on within-species and between species acorn predation, by monitoring 15 mixed forests (450 trees) over seven years. Acorn production in Q. ilex and Q. humilis was highly variable among years, with high population variability (CVp) values. The two species exhibited a very different pattern across years in their initial acorn crop size ( sum of aborted, depredated, and sound acorns). Nevertheless, interannual differences in summer water stress modified the likelihood of abortion during acorn ripening and enforced within-and, particularly, between-species synchrony and population variability in acorn production. The increase in CVp from initial to mature acorn crop ( after summer) accounted for 33% in Q. ilex, 59% in Q. humilis, and 60% in the two species together. Mean yearly acorn pre-dispersal predation by invertebrates was considerably higher in Q. humilis than in Q. ilex. Satiation and starvation of predators was recorded for the two oaks, and this effect was increased by the year-to-year variability in the size of the acorn crop of the two species combined. Moreover, at a longer time scale ( over seven years), we observed a significant reduction in the mean proportion of acorns depredated for each oak and the variability in both species' acorn production combined. Therefore, our results demonstrate that similar patterns of seeding fluctuation over time in coexisting species mediated by an environmental cue ( summer drought) may contribute to the reduction of the impact of seed predation at a within-species level. Future research should be aimed at addressing whether this process could be a factor assisting in the coexistence of Q. ilex and Q. humilis.
Keywords: Curculio spp.; fruit abortion; fruiting synchrony; Mediterranean mixed-oak forests; oaks; predator satiation; Quercus humilis; Quercus ilex; resource matching

Differences in biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) result in similar performance of seedlings of two Mediterranean oaks with contrasting leaf habit - Espelta, Josep Maria; Cortés, Pilar; Mangirón, Marta Retana, Javier (Ecoscience, 2005)
Co-occurrence of winter-deciduous and evergreen oaks is common in some Mediterranean-type climate areas. However, whether these species show an overlap in their regeneration niche is still poorly understood. We explored experimentally the changes in survival, growth, biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) in seedlings of a deciduous oak (Quercus cerrioides) and an evergreen oak (Quercus ilex) in response to co-variation in light and water availability. Quercus cerrioides exhibited higher root length, root area, leaf nitrogen content, and less negative δ13C, but lower leafiness than Q. ilex. The interaction between species and light in specific leaf area and root–shoot ratio indicated different mechanisms to overcome water stress in the two oaks, with Q. ilex relying on leaf hardening and Q. cerrioides relying on a high root–shoot ratio. However, the two species showed similar survival and growth in most of the light–water gradient. Ecological inference of these results indicates that seedlings of these species have a similar ability to cope with variations in light and water in spite of their contrasting leaf habit. This similar performance suggests a competition for similar micro-sites during establishment, rather than a partitioning of the regeneration niche.
Keywords: deciduous; evergreen; Mediterranean-type climate; Quercus cerrioides; Quercus ilex; Regeneration

Differences in biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) result in similar performance of seedlings of two Mediterranean oaks with contrasting leaf habit - Espelta, Josep Maria; Cortés, Pilar; Mangirón, Marta Retana (Ecoscience, 2005)
Co-occurrence of winter-deciduous and evergreen oaks is common in some Mediterranean-type climate areas. However, whether these species show an overlap in their regeneration niche is still poorly understood. We explored experimentally the changes in survival, growth, biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) in seedlings of a deciduous oak (Quercus cerrioides) and an evergreen oak (Quercus ilex) in response to co-variation in light and water availability. Quercus cerrioides exhibited higher root length, root area, leaf nitrogen content, and less negative δ13C, but lower leafiness than Q. ilex. The interaction between species and light in specific leaf area and root–shoot ratio indicated different mechanisms to overcome water stress in the two oaks, with Q. ilex relying on leaf hardening and Q. cerrioides relying on a high root–shoot ratio. However, the two species showed similar survival and growth in most of the light–water gradient. Ecological inference of these results indicates that seedlings of these species have a similar ability to cope with variations in light and water in spite of their contrasting leaf habit. This similar performance suggests a competition for similar micro-sites during establishment, rather than a partitioning of the regeneration niche.
Keywords: deciduous; evergreen; Mediterranean-type climate; Quercus cerrioides; Quercus ilex; Regeneration

Effects of a nursery CO 2 enriched atmosphere on the germination and seedling morphology of two Mediterranean oaks with contrasting leaf habit - Cortés, Pilar; ESPELTA, J M; Save, Robert; Biel, C (New Forests, 2004)
The use of an enriched CO2 atmosphere in tree nurseries has been envisaged as a promising technique to increase productivity and to obtain seedlings with a higher root/shoot ratio, an essential trait to respond to water stress in Mediterranean-type ecosystems. In that framework, we have analyzed the effects of three levels of atmospheric CO2 concentration (350, 500 and 700 ppm) on the germination rate, growth and morphology of seedlings of two Mediterranean oaks used in reforestation programs: the evergreen Quercus ilex L. and the deciduous Quercus cerrioides Wilk. et Costa. CO2 enrichment increased the germination rate of Q. cerrioides (from 70 7 to 81 3%) while it decreased that of Q. ilex (from 71 10 to 41 12%). Seedlings of both species increased approximately 60% their total biomass in response to CO2 enrichment but at two different CO2 concentrations: 500 ppm for Q. cerrioides and 700 ppm for Q. ilex. This increase in seedlings biomass was entirely due to an augmentation of root biomass. Considering germination and biomass partitioning, an enriched CO2 atmosphere might not be appropriate for growing Mediterranean evergreen oaks, such as Q. ilex, since it reduces acorn germination and the only gains in root biomass occur at a high concentration (700 ppm). On the other hand, a moderate CO2 enrichment (500 ppm) appears as a promising nursery technique to stimulate the germination, growth and root/shoot ratio of deciduous oaks, such as Q. cerrioides
Keywords: Forest restoration; Mediterranean-type ecosystems; Nursery techniques; Quercus cerrioides; Quercus ilex; Wildﬁre

Effects of a nursery CO 2 enriched atmosphere on the germination and seedling morphology of two Mediterranean oaks with contrasting leaf habit - Cortés, Pilar; Espelta, J. M.; Save, Robert; Biel, C. (New Forests, 2004)
The use of an enriched CO2 atmosphere in tree nurseries has been envisaged as a promising technique to increase productivity and to obtain seedlings with a higher root/shoot ratio, an essential trait to respond to water stress in Mediterranean-type ecosystems. In that framework, we have analyzed the effects of three levels of atmospheric CO2 concentration (350, 500 and 700 ppm) on the germination rate, growth and morphology of seedlings of two Mediterranean oaks used in reforestation programs: the evergreen Quercus ilex L. and the deciduous Quercus cerrioides Wilk. et Costa. CO2 enrichment increased the germination rate of Q. cerrioides (from 70 7 to 81 3%) while it decreased that of Q. ilex (from 71 10 to 41 12%). Seedlings of both species increased approximately 60% their total biomass in response to CO2 enrichment but at two different CO2 concentrations: 500 ppm for Q. cerrioides and 700 ppm for Q. ilex. This increase in seedlings biomass was entirely due to an augmentation of root biomass. Considering germination and biomass partitioning, an enriched CO2 atmosphere might not be appropriate for growing Mediterranean evergreen oaks, such as Q. ilex, since it reduces acorn germination and the only gains in root biomass occur at a high concentration (700 ppm). On the other hand, a moderate CO2 enrichment (500 ppm) appears as a promising nursery technique to stimulate the germination, growth and root/shoot ratio of deciduous oaks, such as Q. cerrioides
Keywords: Forest restoration; Mediterranean-type ecosystems; Nursery techniques; Quercus cerrioides; Quercus ilex; Wildﬁre

The role of disturbance in the co-existence of the evergreen Quercus ilex and the deciduous Quercus cerrioides - Bonfil, Consuelo; Cortés, Pilar; Espelta, Josep Maria; Retana, Javier (Journal of Vegetation Science, 2004)
Question: Which is the response of the evergreen Quercus ilex and the deciduous Q. cerrioides to repeated disturbances? Location: central Catalonia (northeastern Spain), in the areas affected by two of the largest historically recorded wildfires in NE Spain: the Bages-Berguedà fire (24 300 ha forested area burned in July 1994), and the Solsonès fire (14 300 ha burned in 1998). Methods: Survival and growth of individuals of Quercus ilex and Q. cerrioides were evaluated in plants subjected to different fire histories and experimental disturbances (burning, cutting or clipping) applied either before or after summer. Results: Survival was high (> 99%), with both species showing a similar high resistance to disturbances. Growth after experimental disturbance was positively related to the size of the individual before the latest forest fire occurred. Fire history had a large effect on resprout growth, as the repeated incidence of disturbances lowered the capacity of individuals to grow. The type and season of experimental disturbance experienced by plants had a large effect. Individuals that experienced total above-ground loss had lower growth rates than those with partial loss. A similar pattern was observed in individuals disturbed after the summer in relation to those disturbed before summer. Conclusions: The larger growth rates recorded in Q. cerrioides across all fire histories and experimental treatments, and the higher vulnerability of Q. ilex to increased fire frequency, intensity of experimental disturbance, and disturbance season, provide evidence for the relatively high susceptibility of the latter to repeated disturbances. This view disagrees with the larger resilience of this species compared to co-existing deciduous oaks, as reported.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Burning; clipping; fire; Growth; Mediterranean Region; Quercus; resilience; resprouting; Survival

The role of disturbance in the co-existence of the evergreen Quercus ilex and the deciduous Quercus cerrioides - Bonfil, Consuelo; Cortés, Pilar; Espelta, Josep Maria; Retana, Javier (Journal of Vegetation Science, 2004)
Question: Which is the response of the evergreen Quercus ilex and the deciduous Q. cerrioides to repeated disturbances? Location: central Catalonia (northeastern Spain), in the areas affected by two of the largest historically recorded wildfires in NE Spain: the Bages-Berguedà fire (24 300 ha forested area burned in July 1994), and the Solsonès fire (14 300 ha burned in 1998). Methods: Survival and growth of individuals of Quercus ilex and Q. cerrioides were evaluated in plants subjected to different fire histories and experimental disturbances (burning, cutting or clipping) applied either before or after summer. Results: Survival was high (> 99%), with both species showing a similar high resistance to disturbances. Growth after experimental disturbance was positively related to the size of the individual before the latest forest fire occurred. Fire history had a large effect on resprout growth, as the repeated incidence of disturbances lowered the capacity of individuals to grow. The type and season of experimental disturbance experienced by plants had a large effect. Individuals that experienced total above-ground loss had lower growth rates than those with partial loss. A similar pattern was observed in individuals disturbed after the summer in relation to those disturbed before summer. Conclusions: The larger growth rates recorded in Q. cerrioides across all fire histories and experimental treatments, and the higher vulnerability of Q. ilex to increased fire frequency, intensity of experimental disturbance, and disturbance season, provide evidence for the relatively high susceptibility of the latter to repeated disturbances. This view disagrees with the larger resilience of this species compared to co-existing deciduous oaks, as reported.
Keywords: Burning; clipping; fire; Growth; Mediterranean Region; Quercus; resilience; resprouting; Survival